Kaj je novega v avtobiografiji? - Kopczyk, Michał (Slavistična revija, 2025)
The article discusses various phenomena related to autobiography as treated in Polish literary studies, particularly the branch that applies the methodological approach developed within the framework of cultural literary theory. The author presents the characteristic features of autobiography and the transformations that have taken place in this field. The starting point is the observation that there has been a revival in the study of autobiography, evidenced by the increasing number of published autobiographical works and literary scholars’ growing interest in this form of expression. The article outlines the key assumptions of cultural literary theory and the most compelling examples of its application in the analysis of autobiographical material in the author’s view.
Keywords: autobiography; avtobiografija; cultural literary theory; kulturna literarna teorija; osebnodokumentarna literatura; personal documentary literature; Polish literary studies; poljska literarna veda